Goniometric measurements of the forelimb and hindlimb joints in sheep - Govoni, V. M. [UNESP]; Rahal, Sheila Canevese [UNESP]; Agostinho, F. S. [UNESP]; Conceicao, R. T. [UNESP]; Tsunemi, M. H. [UNESP]; El-Warrak, A. O. (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2012)
Objectives: The aim of this study was to evaluate angle-of-motion values for the forelimb and hindlimb in clinically healthy adult Santa Ines sheep by means of a standard goniometer.Methods: Twenty female Santa Ines sheep, ranging in age between three- to six-years-old, and weighing 32-45 kg (mean +/- standard deviation [SD]: 30.4 +/- 3.7) were used. A standard transparent plastic goniometer was used to measure passive maximum flexion, maximum extension, and range-of-motion (ROM) of the shoulder, elbow, carpal, hip, stifle, and tarsal joints in the right and left limbs. The goniometric measurements were done with the sheep awake and in a standing position. The measurements were made in triplicate by two independent investigators.Results: In all evaluated joints, there was no significant difference either between the means of the two sides or between measurements performed by the two investigators. The mean +/- SD values of the measurements (degrees) were as follows: 20 +/- 1 (flexion), 170 +/- 2 (extension), and 150 +/- 2 (ROM) for the carpal joint; 34 +/- 4 (flexion), 145 +/- 6 (extension), and 110 +/- 4 (ROM) for the elbow joint; 88 +/- 2 (flexion), 144 +/- 6 (extension), and 56 +/- 5 (ROM) for shoulder joint; 35 +/- 4 (flexion), 163 +/- 3 (extension), and 129 +/- 4 (ROM) for tarsal joint; 46 +/- 4 (flexion), 146 +/- 6 (extension), and 100 +/- 4 (ROM) for the stifle joint; 54 +/- 3 (flexion), 143 +/- 7 (extension), and 89 +/- 5 (ROM) for the hip joint.Clinical significance: The data obtained provide useful and objective information on the joints. More studies are necessary using other sheep breeds.
Keywords: Sheep; angle; joint; goniometry